2011
DOI: 10.1177/0267659111408756
|View full text |Cite
|
Sign up to set email alerts
|

Brain damage and cardiopulmonary bypass: is there really any association?

Abstract: Brain damage, in the form of stroke and cognitive deficit associated with heart surgery, has long been attributed unquestioningly to cardiopulmonary bypass (CPB). The aim of this paper is to review the randomised control trials (RCT), systematic reviews and meta-analyses of studies, comparing patients who have undergone on- or off-pump coronary artery bypass grafting (CABG) surgeries that have used stroke or cognition as an outcome to determine whether CPB is associated with brain damage. Although not definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…44 Others report that, in general, there is no increased nonfatal stroke risk in on-pump in comparison with off-pump CABG surgery. 45 There is also little support for a group difference in POCD incidence according to a systematic review 46 and a recent meta-analysis. 6 However, another meta-analysis found that on-pump surgery increased the incidence of POCD at early (1-2 weeks and 3 months) but not later (6 months and 12 months) stages in recovery following CABG surgery 45 ; moreover there is evidence that this lack of a 'late' effect persists at 5 years.…”
Section: Hogan Et Al Fixing Hearts and Protecting Minds 163mentioning
confidence: 99%
“…44 Others report that, in general, there is no increased nonfatal stroke risk in on-pump in comparison with off-pump CABG surgery. 45 There is also little support for a group difference in POCD incidence according to a systematic review 46 and a recent meta-analysis. 6 However, another meta-analysis found that on-pump surgery increased the incidence of POCD at early (1-2 weeks and 3 months) but not later (6 months and 12 months) stages in recovery following CABG surgery 45 ; moreover there is evidence that this lack of a 'late' effect persists at 5 years.…”
Section: Hogan Et Al Fixing Hearts and Protecting Minds 163mentioning
confidence: 99%
“…Связь между операциями на сердце и увеличением частоты церебральных осложнений стала очевидной с развитием кардиохирургии. Тенденцией последних лет стало изучение так называемых минимальных нев рологических дисфункций, включающих нарушение когнитивных способностей (краткосрочная и долговременная память, концентрация внимания, мыслительная функция) и изменение психики (нарушение сна, депрессии, галлюцинации) [1]. Нет полного понимания этиологии поражения мозга при операциях на сердце, не выработан единый подход к профилактике, использованию нейромониторинга, ранней диагностике и лечению неврологических осложнений вмешательств с искусственным кровообращением (ИК) и на работающем сердце [2,3].…”
Section: Introductionunclassified
“…Although an extensive literature base has examined the relative merits of CABG, the impact of CABG or valve operation on changes in cognitive and cerebral function remains a source of controversy [3]. Postoperative cognitive decline has been observed in more than 20% of individuals undergoing cardiac operation [4][5][6], and the extent to which these cognitive changes may be attributable to individual differences [7,8] Despite the wide range of studies that examined cognitive changes after cardiac operation [4][5][6]10], few studies have characterized changes in cerebral perfusion after CABG [11,12] or valve replacement or repair, and no studies have done so using a matched control group with coronary artery disease (CAD). Because individual differences in underlying CAD explain a substantial amount of postoperative cognitive change [10,13], matched control studies that used individuals with CAD and CAD risk factors are important in delineating the relating influence of cardiac operation versus underlying CAD on cognitive changes [14].…”
mentioning
confidence: 99%